Lutetium Copper@Hexagonal Boron Nitride Nanocomposite Electrode System for Sensing and Signalling Ciprofloxacin - Collen Nepfumbada; Prof. Bhekie B. Mamba; Prof. Bart M. Bartlett; Prof. Jorge F. Fernández‐Sánchez; Prof. Usisipho Feleni (ChemElectroChem)
Abstract Herein, a new electrochemical sensing system based on lutetium copper nanoparticles supported on hexagonal boron nitride (Lu‐Cu@h‐BN) was designed for the sensitive detection of ciprofloxacin (CIP) antibiotic. A simple hydrothermal method was used to synthesize the nanocomposite. The structural and morphological characteristics of the as‐prepared nanocomposite were investigated using various analytical techniques such as Fourier transform infrared spectroscopy (FTIR), X‐ray diffraction (XRD), scanning electron microscopy (SEM), and X‐ray photoelectron spectroscopy (XPS). The newly developed Lu‐Cu@h‐BN nanocomposite was used as an electrode modifier for sensing and signalling of CIP. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were used to study the electrochemical activities of the bare GCE, Cu‐h‐BN/GCE, Lu‐h‐BN/GCE, Lu‐Cu/GCE, and Lu‐Cu@h‐BN/GCE. The electro‐oxidation of CIP on electrode surface exhibited an irreversible, diffusion‐controlled process. The sensor system obtained a wider linear range of (0.05–100 μM) with a lower detection limit value of 0.03 μM and sensitivity 0.7443 μA μM−1 cm−2. Furthermore, the sensor demonstrated an excellent selectivity, good stability, and reproducibility, with acceptable recoveries of 96 % to 104 % in real water sample analysis.